Teaching and Learning for Critical Reflection on Diversity: The Need to Go Beyond the Western Perspective in a Doctoral Program in Adult Education - Maria Liu Wong; Lyle Yorks (Adult Education Research Conference, 2014)
In an increasing inter-connected world, cultural sensitivity and leveraging diversity are critical to leadership practice. This paper examines how a cohort-based adult education doctoral program addressed diversity in teaching and learning. Including non-Western perspectives on adult learning and providing space for critical reflection equip students in a ‘global educator narrative.’